Weed Control in Bulb Crops (Onion, Leek, Garlic, Shallot) - William M. Stall (EDIS)
Revised! HS193, a 3-page fact sheet by William M. Stall, provides updated recommendations for weed control in bulb crops. Published by the UF Department of Horticultural Sciences, March 2010.